Excludentes no Código de Defesa do Consumidor: o tratamento das hipóteses caso fortuito, força maior e riscos de desenvolvimento - Bosch, Marcia Helena (2009)
This study aims to demonstrate that the idea which seems right on the exclusive responsibility of the relations of consumption that is the view that if the code of consumer protection does not expressly contemplate the fortuitous event and force majeure as the exclusive responsibility, not it is for the interpreter do it. Also discusses the fact that in cases of force majeure and fortuitous event refers, in fact, the fault of the agent (and not the causal link) and the code is the responsibility of consumer protection, as a rule, objective, which investigates the fault is not the best exegesis seems once again be the case that excludes the fortuitous and exclusive as forces greater responsibility in the relations between suppliers and consumers